Anisotropic structure of the Australian continent - Birkey, Andrew; Ford, Heather A. (Frontiers in Earth Science, 2023)
The Australian continent preserves some of the oldest lithosphere on Earth in the Yilgarn, Pilbara, and Gawler Cratons. In this study we present shear wave splitting and Ps receiver function results at long running stations across the continent. We use these results to constrain the seismic anisotropic structure of Australia’s cratons and younger Phanerozoic Orogens. For shear wave splitting analysis, we utilize SKS and SKKS phases at 35 broadband stations. For Ps receiver function analysis, which we use to image horizontal boundaries in anisotropy, we utilize 14 stations. Shear wave splitting results at most stations show strong variations in both orientation of the fast direction and delay time as a function of backazimuth, an indication that multiple layers of anisotropy are present. In general, observed fast directions do not appear to be the result of plate motion alone, nor do they typically follow the strike of major tectonic/geologic features at the surface, although we do point out several possible exceptions. Our Ps receiver function results show significant variations in the amplitude and polarity of receiver functions with backazimuth at most stations across Australia. In general, our results do not show evidence for distinctive boundaries in seismic anisotropy, but instead suggest heterogenous anisotropic structure potentially related to previously imaged mid-lithospheric discontinuities. Comparison of Ps receiver function and shear wave splitting results indicates the presence of laterally variable and vertically layered anisotropy within both the thicker cratonic lithosphere to the west, as well as the Phanerozoic east. Such complex seismic anisotropy and seismic layering within the lithosphere suggests that anisotropic fabrics may be preserved for billions of years and record ancient events linked to the formation, stabilization, and evolution of cratonic lithosphere in deep time.